Cultures of violence : Lynching and Racial Killing in South Africa and the American South. - Evans, Ivan (Manchester University Press, 2007)
This book deals with the inherent violence of?race relations? in two important countries that remain iconic expressions of white supremacy in the twentieth century. *Cultures of violence* does not just reconstruct the era of violence. Instead it convincingly contrasts the?lynch culture? of the American South to the?bureaucratic culture of violence? in South Africa. By contrasting mobs of rope-wielding white Southerners to the gun-toting policemen and administrators who formally defended white supremacy in South Africa, *Cultures of violence* employs racial killing as an optic for examining t.